2017
DOI: 10.1160/th17-03-0166
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of a glycoPEGylated rFVIII (turoctocog alpha pegol, N8-GP) in paediatric patients with severe haemophilia A

Abstract: Turoctocog alfa pegol (N8-GP, Novo Nordisk, Bagsværd, Denmark), an extended half-life glycoPEGylated recombinant factor VIII (rFVIII), is being developed for prophylaxis and treatment of bleeds in haemophilia A patients. pathfinder™5 is a multinational, open-label, single-arm trial to assess safety, efficacy and pharmacokinetics of N8-GP in paediatric (<12 years), previously treated patients. Boys with severe haemophilia A (<1 % FVIII), no history of inhibitors and previously treated with FVIII products (>50 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
114
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(120 citation statements)
references
References 21 publications
(29 reference statements)
5
114
0
1
Order By: Relevance
“…However, indirect comparisons can also provide useful information on the possible trend in PK parameters across products. Based on available published data, BAY 94‐9027 appears to have a comparable or improved PK profile, including t ½ and AUC, in all patient age groups vs other extended‐half‐life rFVIII products by indirect comparison …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, indirect comparisons can also provide useful information on the possible trend in PK parameters across products. Based on available published data, BAY 94‐9027 appears to have a comparable or improved PK profile, including t ½ and AUC, in all patient age groups vs other extended‐half‐life rFVIII products by indirect comparison …”
Section: Discussionmentioning
confidence: 99%
“…Based on available published data, BAY 94-9027 appears to have a comparable or improved PK profile, including t ½ and AUC, in all patient age groups vs other extended-half-life rFVIII products by indirect comparison. 19,20,29,30 During prophylactic replacement therapy, increased time per week spent with low FVIII levels (<1%) is known to be a determinant of breakthrough bleeding risk, especially in children. 31 Similarly, time spent with FVIII levels >20%, high FVIII peak levels and AUC have been associated with reduced bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…While these findings illustrate that PEGylation appears to influence contact activation by silica, it is important to note that there are no clinical consequences of this modification as the efficacy of N8-GP has been demonstrated in a number of studies [13][14][15]. Both PEGylated and unmodified rFVIII products exhibited a similar degree of adsorption to silica particles, suggesting that contact activation may not be blocked through specific adherence of the PEGylated molecule to the silica surface.…”
mentioning
confidence: 78%
“…2,6,7 Variations in assay results appear to be related to the type of contact activator used in the APTT reagent, with some silica-based APTT reagents underestimating the activity of extended half-life rFVIII molecules. [13][14][15] N8-GP can be administered every 4th day, reducing the burden of frequent prophylactic treatment. 5 It is therefore important to identify assays that can be used to accurately monitor clinical postadministration samples and to communicate information regarding the most appropriate assays to use for monitoring to the clinical laboratories that perform these tests.…”
Section: Introductionmentioning
confidence: 99%
“…In a pediatric cohort (68 PTPs < 12 years), N8-GP was tested in a twice weekly prophylactic regimen [34]. More than 40% of patients did not report any bleeding during trial phase and reported median ABR was 1.95 (IQR 0.00-2.79).…”
Section: Fviii Products (mentioning
confidence: 99%